2017
DOI: 10.1101/191015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Catecholaminergic modulation of the avoidance of cognitive control

Abstract: Abstract:The catecholamines have long been associated with cognitive control and value-based decision-making. More recently, we proposed that the catecholamines might modulate value-based decision-making about whether or not to engage in cognitive control. We test this hypothesis by assessing effects of a catecholamine challenge in a large sample of young, healthy adults (n = 100) on the avoidance of a cognitively demanding control process: task switching. Prolonging catecholamine transmission by blocking reup… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 135 publications
1
14
0
Order By: Relevance
“…Specifically, the (demand-induced) subjective value of control decreased with tyrosine administration in participants with high baseline impulsivity, while it was increased, if anything, in less impulsive participants. This interaction between drug status and impulsivity is a small effect, but interesting because it mirrors a similar interaction between the catecholamine agonist methylphenidate and impulsivity in our previous study that had greater statistical power to assess individual differences (n = 100) (4). In that study, participants with low impulsivity showed neutral or even reduced avoidance of cognitive demand, while those with high baseline impulsivity increased demand avoidance when given methylphenidate.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Specifically, the (demand-induced) subjective value of control decreased with tyrosine administration in participants with high baseline impulsivity, while it was increased, if anything, in less impulsive participants. This interaction between drug status and impulsivity is a small effect, but interesting because it mirrors a similar interaction between the catecholamine agonist methylphenidate and impulsivity in our previous study that had greater statistical power to assess individual differences (n = 100) (4). In that study, participants with low impulsivity showed neutral or even reduced avoidance of cognitive demand, while those with high baseline impulsivity increased demand avoidance when given methylphenidate.…”
Section: Discussionsupporting
confidence: 61%
“…According to the expected value of control account, people recruit cognitive control in proportion to expected instrumental value (3), such that degree (and intensity) of engagement in an upcoming cognitive computation is based on a cost-benefit analysis. Recently, we demonstrated that acute administration of a single oral dose of the catecholamine transporter blocker methylphenidate indeed modulated the avoidance of, but not ability to perform cognitive control in young adults (4). The effect depended on trait impulsivity, with the most impulsive subjects exhibiting the greatest increases in control avoidance.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Beyond altering control performance, DA can also increase the degree to which individuals explicitly choose to avoid high versus low control-demanding tasks. Specifically, the DA transporter blocker methylphenidate caused high trait-impulsive participants to avoid control demands more [38], suggesting that DA may undermine control by altering when individuals choose to exert it.…”
Section: Da Also Undermines Controlmentioning
confidence: 99%